2012
DOI: 10.1038/bmt.2012.30
|View full text |Cite
|
Sign up to set email alerts
|

Traumeel S in preventing and treating mucositis in young patients undergoing SCT: a report of the Children's Oncology Group

Abstract: Mucositis can be a serious complication of hematopoietic SCT (HSCT). A previous phase II trial in 32 children undergoing HSCT reported a beneficial effect of the homeopathic remedy Traumeel S. The Children’s Oncology Group sought to replicate the results in a multi-institutional trial. The study was an international multi-center, double-blind, randomized trial comparing Traumeel with placebo in patients aged 3–25 years undergoing myeloablative HSCT. Traumeel/placebo was started on Day −1 as a five-time daily m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 38 publications
0
31
0
2
Order By: Relevance
“…Table shows other complementary health approaches . A small RCT was performed testing the efficacy of Traumeel S (homeopathy) in reducing the incidence of chemotherapy‐induced stomatitis in pediatric patients undergoing HCT .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table shows other complementary health approaches . A small RCT was performed testing the efficacy of Traumeel S (homeopathy) in reducing the incidence of chemotherapy‐induced stomatitis in pediatric patients undergoing HCT .…”
Section: Resultsmentioning
confidence: 99%
“…There appeared to be relatively few studies testing natural products and alternative systems of medicine such as homeopathy and there were no published studies on Ayurvedic medicine. Literature exists regarding exaggerated intervention effect sizes in RCTs with a small sample size, resulting in discrepancies with the results of large RCTs, a finding that was observed in studies on Traumeel S in patients undergoing HCT . SAEs were not reported in the majority of studies, which could be due to small sample size or underreporting, among other factors.…”
Section: Discussionmentioning
confidence: 98%
“…In cancer care the effect of this compound is Integr Cancer Sci Therap, 2016 doi: 10.15761/ICST.1000188 controversial. One small single-center trial reported a beneficial effect of Traumeel S on chemotherapy-induced mucositis compared with placebo [49] whereas a multi-center, double-blind, placebo-controlled randomized trial did not confirm these positive results [50]. However, a trend towards less narcotic usage in the Traumeel-arm group was still observed.…”
Section: Homeopathymentioning
confidence: 77%
“…36 Excellent compliance may be related to a once-daily administration, a small amount of liquid and a highly motivated patient population as many patients undergoing HCT self-prescribe probiotic therapy. These results suggest that if probiotics are found to be effective and safe, patients may be largely compliant to probiotic therapy because of the perceived benefits of probiotics and its extensive safety profile.…”
Section: Discussionmentioning
confidence: 99%